(untitled) (Repertorio Americano, 2022)
The present work aims at exploring the roots of ekphrastic poetry: the convergence of graphic art and its verbal representation. In the light of this tradition, this ambitious historical endeavor prances through centuries, from Homer’s description of the making of the shield of Achilles in the Iliad to modern ekphrastic poetry in order to have a better understanding of this practice, so old yet so unconversant. It will focus on the ekphrastic custom of prosopopoeia as a means of unsilencing the gazee and in which its narrativity will both speak out and pour the poet’s verbality. The ekphrastic poem becomes a junction of painter, poet, reader, and work of art in order to bring the signifier into being in this rendezvous of minds.